P2RY12-Inhibitors Reduce Cancer-Associated Thrombosis and Tumor Growth in Pancreatic Cancers - Palacios-Acedo, Ana Luisa; Mezouar, Soraya; Mège, Diane; Crescence, Lydie; Dubois, Christophe; Panicot-Dubois, Laurence (Frontiers in Oncology, 2021)
Platelet function can be modified by cancer cells to support tumor growth, causing alterations in the delicate hemostatic equilibrium. Cancer-cell and platelet interactions are one of the main pillars of Trousseau’s syndrome: a paraneoplastic syndrome with recurring and migrating episodes of thrombophlebitis. Altogether, this leads to a four-fold risk of thrombotic events in cancer patients, which in turn, portend a poor prognosis. We previously demonstrated that anti-P2RY12 drugs inhibit cancer-associated-thrombosis and formation of tumor metastasis in pancreatic cancer models. Here, we aimed to (1) compare the effects of aspirin and clopidogrel on pancreatic cancer prevention, (2) characterize the effects of clopidogrel (platelet P2RY12 inhibitor) on cancer-associated thrombosis and cancer growth in vivo, (3) determine the effect of P2RY12 across different digestive-tract cancers in vitro, and (4) analyze the expression pattern of P2RY12 in two different cancer types affecting the digestive system. Clopidogrel treatment resulted in better survival rates with smaller primary tumors and less metastasis than aspirin treatment. Clopidogrel was also more effective than aspirin at dissolving spontaneous endogenous thrombi in our orthotopic advanced cancer mouse model. P2RY12 expression gives pancreatic adenocarcinomas proliferative advantages. In conclusion, we propose the hypothesis that clopidogrel should be further studied to target and prevent Trousseau’s syndrome; as well as diminish cancer growth and spread. However, more studies are required to determine the implicated pathways and effects of these drugs on cancer development.